Tremor associated with similar structural networks in Parkinson's disease and essential tremor - Filip, Pavel; Burdová, Kristína; Valenta, Zdeněk; Jech, Robert; Kokošová, Viktória; Baláž, Marek; Mangia, Silvia; Michaeli, Shalom; Bareš, Martin; Vojtíšek, Lubomír (Parkinsonism & related disorders, 2022)
INTRODUCTION: Despite substantial clinical and pathophysiological differences, the characteristics of tremor in Parkinson's disease (PD) and essential tremor (ET) patients bear certain similarities. The presented study delineates tremor-related structural networks in these two disorders. METHODS: 42 non-advanced PD patients (18 tremor-dominant, 24 without substantial tremor), 17 ET, and 45 healthy controls underwent high-angular resolution diffusion-weighted imaging acquisition to reconstruct their structural motor connectomes as a proxy of the anatomical interconnections between motor network regions, implementing state-of-the-art globally optimised probabilistic tractography. RESULTS: When compared to healthy controls, ET patients exhibited higher structural connectivity in the cerebello-thalamo-cortical network. Interestingly, the comparison of tremor-dominant PD patients and PD patients without tremor yielded very similar results - higher structural connectivity in tremor-dominant PD sharing multiple nodes with the tremor network detected in ET, despite the generally lower structural connectivity between basal ganglia and frontal cortex in the whole PD group when compared to healthy controls. CONCLUSION: The higher structural connectivity of the cerebello-thalamo-cortical network seems to be the dominant tremor driver in both PD and ET. While it appears to be the only tremor-related network in ET, its combination with large scale hypoconnectivity in the frontal cortico-subcortical network in PD may explain different clinical features of tremor in these two disorders.
Keywords: konektom; Magnetic Resonance Imaging; esenciální tremor; Connectome; magnetická rezonanční tomografie; Tremor; Essential Tremor; Humans; tremor; lidé; Parkinson Disease; Parkinsonova nemoc